Spatio-temporal changes in endosymbiont diversity and composition in the African cassava whitefly, Bemisia tabaci SSA1 - El Hamss, Hajar; Maruthi, M. N.; Ally, Hadija M.; Omongo, Christopher A.; Wang, Hua-Ling; van Brunschot, Sharon; Colvin, John; Delatte, Hélène (Frontiers in Microbiology, 2022)
Sap-sucking insects, including whiteflies, are amongst the most devastating and widely distributed organisms on the planet. They are often highly invasive and endosymbiont communities within these insects help them adapt to new or changing environments. Bemisia tabaci whitefly species are vectors of more than 500 known plant-viruses and harbour highly diverse endosymbionts communities. To date, however, whitefly-endosymbiont interactions, community structure and their spatio-temporal changes are still poorly understood. In this study, we investigated the spatio-temporal changes in the composition and diversity of bacterial endosymbionts in the agricultural crop pest whitefly species, B. tabaci Sub-Saharan Africa 1-sub group 1 (SSA1-SG1). 16S rDNA amplicon sequencing analysis was carried out to characterise endosymbiont compositions in field-collected SSA1-SG1 populations infesting cassava in Uganda in 1997 and 2017. We detected Portiera, Arsenophonus, Wolbachia, Hamiltonella and Hemipteriphilus, with Arsenophonus and Wolbachia infections being predominant. Hemipteriphilus and Hamiltonella frequencies were very low and were detected in seven and 2 samples, respectively. Bacterial diversity based on three independent parameters including Simpson index, number of haplotypes and Bray Curtis matrix were significantly higher in 1997 than in 2017. This period also coincided with the advent of super-abundant cassava-whitefly populations on cassava crops in Uganda. We discuss how endosymbionts may influence the biology and behaviour of whiteflies leading to population explosions.